Globalization and Poverty in Senegal: A Worst Case Scenario? - Miet Maertens; Liesbeth Colen; Johan F.M. Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2008)
There is no consensus about how globalization -trade and foreign investments ?affects poverty reduction. Using household survey data, this study contributes to the empirical literature on globalization and poverty by analyzing the household-level implications of increased foreign investments and trade in the horticulture sector in Senegal. In many aspects this represents what many would consider a 'worst-case scenario? Stringent rich country standards are imposed on exports and the supply chain is controlled by a single multinational company with extreme levels of supply base consolidation and vertical integration and complete exclusion of smallholder suppliers. We analyze and quantify income and poverty effects under these 'worst-case conditions?and find significant positive welfare impacts through employment creation and labor market participation.
Keywords: F2; J43; O12; Q12; Q17; 330; trade; FDI; poverty; vertical coordination; modern supply chains; Globalisierung; Direktinvestition; Gartenbauprodukt; Außenhandel; Vertikale Konzentration; Wohlfahrtsanalyse; Senegal